1972
DOI: 10.1203/00006450-197205000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Hormonal Responses to Luteinizing Hormone-Releasing Hormone (LH-RH) in Prepubertal and Adult Subjects

Abstract: ExtractLuteinizing hormone-releasing hormone (LH-RH), purified from porcine hypothalamic tissue, was administered in an intravenous dose of 300 /xg to four prepubertal and four adult human subjects. The resulting increases in plasma levels of LH and FSH were statistically significant (P < 0.01) in the 16-and 32-min samples, but did not differ with the age or sex of the subject groups. The mean maximum increase in plasma LH values was 290% for men and 425% for women. Injection of LH-RH resulted in a 500% mean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The pubertal increase of FSH response in boys has been found by Kastin et al (1972), Grumbach et al (1974), Suwa et al (1974), Kelch et al (1975), Dickerman et al (1976) but not by Franchimont et al (1973), Illig et al (1973) and Schonberg et al (1974). In girls, some groups have found that the FSH response does not increase with puberty (Suwa et al, 1974;Grumbach et al, 1974;Schonberg, 1975), while others have found a pubertal increase of FSH stores (Kastin et al, 1972;Franchimont et al, 1973). Recently, Dickerman et al (1976), studying 47 normal girls aged 5-18 years who underwent a 50Mg/m2 LH-RH test, found a sharp increase of FSH response at clinical stage P2, fol lowed by a decrease at stage P3 and a small rise again at stages P4-P5.…”
Section: Lh-rh Test In Normal Children and Adolescentsmentioning
confidence: 83%
See 1 more Smart Citation
“…The pubertal increase of FSH response in boys has been found by Kastin et al (1972), Grumbach et al (1974), Suwa et al (1974), Kelch et al (1975), Dickerman et al (1976) but not by Franchimont et al (1973), Illig et al (1973) and Schonberg et al (1974). In girls, some groups have found that the FSH response does not increase with puberty (Suwa et al, 1974;Grumbach et al, 1974;Schonberg, 1975), while others have found a pubertal increase of FSH stores (Kastin et al, 1972;Franchimont et al, 1973). Recently, Dickerman et al (1976), studying 47 normal girls aged 5-18 years who underwent a 50Mg/m2 LH-RH test, found a sharp increase of FSH response at clinical stage P2, fol lowed by a decrease at stage P3 and a small rise again at stages P4-P5.…”
Section: Lh-rh Test In Normal Children and Adolescentsmentioning
confidence: 83%
“…The pubertal increase of LH response to LH-RH has been found by most authors in boys (Roth et al, 1972Kastin et al, 1972, Thomas et al, 1972Franchi mont et al, 1973Franchi mont et al, , 1974Illig et al, 1973;Suwa et al, 1974;Grumbach et al, 1974;Kelch et al, 1975;Schonberg et al, 1975,Dickerman et al, 1976 and in girls (Franchimont et al, 1973(Franchimont et al, , 1974Grumbach et al, 1974;Suwa et al, 1974;Schonberg et al, 1974;Schonberg, 1975;Dickerman et al, 1976). The pubertal increase of FSH response in boys has been found by Kastin et al (1972), Grumbach et al (1974), Suwa et al (1974), Kelch et al (1975), Dickerman et al (1976) but not by Franchimont et al (1973), Illig et al (1973) and Schonberg et al (1974). In girls, some groups have found that the FSH response does not increase with puberty (Suwa et al, 1974;Grumbach et al, 1974;Schonberg, 1975), while others have found a pubertal increase of FSH stores (Kastin et al, 1972;Franchimont et al, 1973).…”
Section: Lh-rh Test In Normal Children and Adolescentsmentioning
confidence: 94%
“…The present study again demonstrates that in humans, also, LH-RH releases FSH as well as LH (1-3). It does not cause consistent changes in the plasma levels of growth hormone, thyrotropin, or cortisol (13).…”
Section: Methodsmentioning
confidence: 99%
“…Basal serum LH (S-LH) concentrations reflect the course of pubertal development better than serum FSH (S-FSH) levels, as they increase about 50- to 100-fold between prepuberty and adulthood, while the corresponding increase in S-FSH is about 10-fold [1,2]. For more than 40 years, the GnRH test has been considered the reference method for assessing the hypothalamic-pituitary-gonadal (HPG) axis function in pubertal disorders [3,4], because the previously used radioimmunoassay methods did not accurately measure the low basal S-LH and S-FSH levels in prepubertal children. The GnRH test appears to be a better tool for the evaluation of sexual precocity than for delayed puberty [5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%